Single-material organic solar cells with fully conjugated electron-donor alkoxy-substituted bithiophene units and electron-acceptor benzothiadiazole moieties alternating in the main chain. Issue 12 (26th February 2020) - Marinelli, Martina; Lanzi, Massimiliano; Liscio, Andrea; Zanelli, Alberto; Zangoli, Mattia; Di Maria, Francesca; Salatelli, Elisabetta
Abstract : Main chain conjugated linear polymers, constituted by alternating electron-donor (D) and -acceptor (A) moieties, have been prepared with the aim of testing their performances as photoactive components in single material organic solar cells (SMOSCs). Abstract : Main chain conjugated linear polymers, constituted by alternating electron-donor (D) and -acceptor (A) moieties, have been prepared with the aim of testing their performances as photoactive components in single material organic solar cells (SMOSCs). The D moiety is constituted by bithiophene co-units bearing in position 3 of the thiophene ring a hexyloxy, a hexyloxymethyl or a hexyl group, while the A moiety is represented by the benzothiadiazole group. The D–A polymers were obtained in high yield through the poorly demanding oxidative FeCl3 polymerization process – starting, respectively, from the related precursors 4, 7-bis(3-hexyloxythiophen-2-yl)benzo[ c ][2, 1, 3]thiadiazole, 4, 7-bis[3-(6-methoxyhexyl)thiophen-2-yl]benzo[ c ][2, 1, 3]thiadiazole and 4, 7-bis(3-hexylthiophen-2-yl)benzo[ c ][2, 1, 3]thiadiazole – with low dispersity indexes, close to the monodisperse state, after fractionation with methanol. The materials have been thoroughly characterized for their physical and structural properties and then tested for photoconversion efficiency in SMOSCs by using different deposition procedures of the photoactive component. In agreement with Kelvin probe force microscopy (KPFM) measurements, the best photovoltaic performance was observed for the polymer based on conjugated 3-alkoxythiophene and benzothiadiazole moieties, achieving significant photocurrents for this type of fully conjugated alternating D–A structure ( J sc = 2.63–3.72 mA cm −2 ).